APARTEMEN IKAN MODEL TRANSPLANTASI CORAL REEF UPAYA KONSERVASI DAN MENINGKATKAN HASIL TANGKAPAN NELAYAN DI DESA AFULU KABUPATEN NIAS UTARA - Manurung, Vindy Rilani; Susetya, Ipanna Enggar; Arinah, Hafizah; Nurjannah, May Indah; Nazara, Wilman (Universitas Mataram, 2024)
Afulu Village, located in Afulu Sub-district, North Nias Regency, has three interconnected ecosystems: coral reef ecosystem, seagrass ecosystem, and mangrove ecosystem. One of the main problems that occurs in Afulu Village is the damage to the coral reef ecosystem due to destructive activities such as the use of bombs, potassium, and poison by irresponsible people. This damage has caused the fishing grounds to become more distant, resulting in a decline in fishermen's catches from year to year. In addition, earthquakes and sedimentation events also have the potential to have a negative impact on coastal ecosystems such as coral reef ecosystems and mangrove ecosystems. These problems are exacerbated by the lack of community knowledge about coastal area management. To overcome these problems, this service activity aims to provide solutions to increase fishermen's catches through coral reef conservation management efforts. One of the innovations applied is the Science and Technology-based Coral Reef Transplantation Model Fish Apartment. The implementation method includes socialization, training and application of science and technology innovation of coral reef transplantation model fish apartment, as well as mentoring and evaluation. The main target of this activity is the Aman Setia Joint Business Group (KUB), which consists of fishermen groups in Afulu Village, Afulu District, North Nias Regency. It is expected that with the implementation of this activity, fishermen can maximize catches, increase daily income, and be able to disseminate information on science and technology innovations in coral reef transplantation model fish apartments to the people of Afulu Village. This is expected to support the recovery of ecosystem habitats independently and sustainably.